The Influence Of Work Enthusiasm, Job Division, And Competence On Employee Performance With Work Commitment As A Moderating Variable - Awaludin, Awaludin; Basri, Ahmad; Paleni, Herman (UNIVED Press, 2026)
This study aims to analyze the influence of work enthusiasm, job division, and competence on employee performance, with work commitment as a moderating variable. A quantitative research approach was employed, involving a sample of 51 employees of the Social Affairs Office of Musi Rawas Regency. Data were collected through the distribution of structured questionnaires to respondents, and the analytical technique used was Structural Equation Modelling based on Partial Least Squares (SEM-PLS). The results indicate that work enthusiasm has a positive and significant effect on employee performance. Job division also has a positive and significant effect on employee performance. Furthermore, competence exerts a positive and significant influence on employee performance. The findings also confirm that work commitment positively and significantly moderates the relationships between work enthusiasm, job division, and competence on employee performance. This suggests that higher levels of work commitment strengthen the effects of work enthusiasm, effective job division, and adequate competence on employee performance. Overall, the study demonstrates that employee performance at the Social Affairs Office of Musi Rawas Regency is strongly influenced by work enthusiasm, clear and proportional job division, and employee competence, with work commitment playing a crucial role in reinforcing these relationships.